The Efficacy of Protected Areas and Future Challenges for Wildlife Conservation in Sarawak - Jayasilan, Mohd. Azlan; Lawes, M.J (LESTARI Publisher, 2012)
The protected areas of Sarawak now contain the best examples of what were once some of the most diverse and continuous mature rainforest in the world. Excluding proposed sites and marine reserves, Sarawak boasts 26 protected areas comprising nature reserves, wildlife sanctuaries and national parks. These are the only line of defence in efforts to protect Sarawak’s biodiversity and prevent local extinction. The protected areas cover about 0.5 million hectares of forest, or 4% of Sarawak’s total area. Accelerated land conversion to agriculture, agro-forestry and urban development has confined the residual biodiversity to protected areas and human-modified or secondary habitat. With protected areas being fragmented and isolated, even minor threats to these areas could potentially have large impacts on their biodiversity. The ability of species to persist within such remnants is an issue of concern. With the rapid pace of anthropogenic land use change, Sarawak is running out of potential sites for new high quality protected areas. In light of this, and based on past and present experience, a decisive approach to conserving the remaining diverse mature rainforest is urgently needed. New criteria for reserve selection based on basic principles of ecology are critically needed to maximize conservation gains and priorities.